Factors Affecting the Implementation of BIM in a Design Office as Part of the Industry 4.0 Idea - Monika SIEWCZYNSKA; Agnieszka GRZELCZAK (Communications of International Proceedings, 2021)
Modern digital technologies, characteristic of the idea of Industry 4.0, are not reserved only for production companies. Solutions widely used in the world, such as virtual and augmented reality, the Internet of people, things, services and data, remote control and autonomous construction machines or even a data cloud, require a different approach to work and design, and from employees completely new, often higher skills. Technologies used in contemporary design offices in the construction industry are based on BIM systems. And just as rapid computerization in the 1980s contributed to the automation of activities, the BIM revolution affects the activities of the construction industry today through full cooperation between designers of various industries, exchange of 3D model files, use of data for cost estimations and schedules, and in the future it will be conducive to full integration of models with all data available in the cloud, also via mobile applications. The article analyzes the reorganization of the work of a small design office in order to identify the factors influencing the success of BIM implementation.
Keywords: Industry 4.0; building information modeling